Assessment of Adolescent and Youth Friendly Health Services in Sri Lanka using WHO's '4S' Framework. (13th November 2019) - Wickramasinghe, N; Vithana, C; Lokubalasooriya, A; Hemachandra, N
Abstract: Background: The Adolescent and Youth Friendly Health Services (AYFHS) in Sri Lanka (SL) are provided via three service models, viz., hospital-based, field-based and centre-based. This study assessed the implementation status of AYFHS in SL. Methods: A panel of experts conducted the review by adopting a participatory approach. Policies and supporting documents were collected from the relevant sectors of the Ministry of Health using electronic and manual search and by visiting institutions/resource persons. The strengths and weaknesses of the AYFHS were identified using the WHO's '4S' Framework consisting strategic information (S1), supportive evidence-informed policies (S2), strengthening services for adolescents (S3) and strengthening collaboration with other sectors (S4). Results: While recent development of guidelines, standards and protocols in line with WHO/UNAIDS 'Global Standards for Quality Health-care Services for Adolescents' was the main strength on S1, gaps in timeliness, completeness and accuracy of the data; and the gaps in effective utilization of sub-national level data addressing area specific problems were the main weaknesses. On S2, SL has a strong, supportive policy environment to promote adolescent health. Lack of coherence in existing health related policies was the main gap. A comprehensive health care package was a strength on S3, while difficulty in reaching the vulnerable groups, curative service oriented service package and underutilization of the health services by adolescents were the weaknesses. On S4, lack of sustained political commitment identifying adolescent health as a priority development issue across multi-stakeholders and their silo mentality to maintain the accountability/ownership of cross-cutting programmatic activities were the weaknesses. Conclusions: Despite numerous imposing challenges, with mainstreaming and constructive monitoring, the AYFHS in SL will remain as one of the best adolescent health programmes in the region. Key messages: Assessment of Sri Lankan AYFHS according to the WHO's '4S' Framework revealed multiple strengths such as updated guidelines, supportive policy environment and comprehensive care package. Despite numerous imposing challenges, with mainstreaming and constructive monitoring, the AYFHS in SL will remain as one of the best adolescent health programmes in the region.